The Development of Pisa-Based Buffer Solutions and Its Application Using the Kahoot Platform - Abdul Gani; Muhammad Nazar; Qurratun ‘Akyun (Postgraduate, University of Mataram, 2022)
An innovation in media technology that can be used in the field of education is Kahoot. Kahoot is an online application in the form of a platform. Kahoot app as a learning technology platform can combine the implementation of interactive quizzes. The problems that exist in SMA Negeri 3 Banda Aceh for students in learning chemistry are about understanding concepts that are still lacking. For this reason, it is necessary to conduct research on